Pemberian ASI Eksklusif dan Imunisasi Dasar dengan Kejadian Stunting Pada Balita - Taswin, Taswin; Taufiq, La Ode Muh.; Damayanti, Wa Ode Astika; Subhan, Muhammad (Jurnal Kebidanan Malakbi, 2023)
There were 344 cases of stunting under five at the Pasarwajo Health Center, Pasarwajo Village, Buton Regency, Southeast Sulawesi Province. Stunting in Pasarwajo Village is ranked 2nd out of 10 Villages in Pasarwajo District with a total of 46 cases in 2021. Stunting is a result of stunted growth processes. Stunting is still a nutritional problem that needs attention. The problem of stunting is directly influenced by exclusive breastfeeding which is related to the child's nutrition and nutritional intake, as well as basic weaknesses related to the child's immunity to a disease. The purpose of this study was to determine the relationship between exclusive breastfeeding and basic immunization with the incidence of stunting in toddlers aged 9-59 months in Pasarwajo Village, Buton Regency. This research method is a quantitative research with a cross sectional study approach. The total population is 325 toddlers with toddlers' mothers as respondents. Sampling using probability random sampling technique, obtained a sample of 78 toddlers. The results of this study indicate that there is a relationship between exclusive breastfeeding (Ï-0.004 <0.05) and the incidence of stunting in the Pasarwajo sub-district, Buton Regency, and there is a relationship between basic deprivation (Ï-0.009 <0.05) and the incidence of stunting in the Pasarwajo sub-district, Kabupaten Buton. The conclusion of the study is that there is a relationship between exclusive breastfeeding and basic activating with the incidence of stunting in toddlers aged 9-59 months in Pasarwajo Village, Buton Regency.